Examining factors that influence a woman's search for information about menopause using the socio-ecological model of health promotion. (October 2018) - Cooper, Jamie
Highlights: Women indicate they need more information about menopause than they receive. Foreknowledge of menopause most often leads to a more positive attitude, which leads to a more positive menopause experience. Fewer than half of the participants in this study indicated that they had engaged in any kind of learning about menopause. Factors influencing self-directed learning were found at every level of the socio-ecological model of health promotion. There is a need to connect adult education with health promotion, at every level of the socio-ecological model. Abstract: Recognizing that increased knowledge of the perimenopause transition, in advance of experiencing symptoms, can make a positive impact on a woman's menopause experience, this study investigated whether women engage in self-directed learning to inform themselves about menopause, and if they do initiate self-directed learning, what socio-ecological issues may help or hinder their search. Two hundred twenty-seven responses to an online survey were analyzed from women aged 35–55 years. Fewer than half (48%) indicated that they had engaged in any kind of learning action regarding menopause. For the women who initiated a search to know more about their bodies at menopause, factors influencing their self-directed learning actions were found at every level of the socio-ecological model (SEM) of health promotion: intrapersonal, interpersonal, institutional, community, and policy factors. In general, women indicate they need more information than they receive. However, in this study the interpersonal level was the only level whose factors provided respondents with more help than hindrance. At all other levels, women were hindered from gaining the knowledge they need. From feelings of embarrassment to feelings of neglect by health care providers, women struggled to gain the information they sought. Understanding that education is one of the key determinants of health, the most important implication of the results of this study is that there is a need to connect adult education with health promotion, at every level of the socio-ecological model of health promotion.